THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHER IN SHAPE THE PERSONALITY OF CLASS IV STUDENTS AT SD AL HILAAL SIWAR DISTRICT AMBALAU BURU SELATAN - Siti Mahu Mahu; Andi Rahmat Abidin (Kuttab: Jurnal Ilmiah Mahasiswa, 2022)
Al hilaal Siwar Elementary School (SD) is one of the elementary level schools located in Siwar Village, Ambalau District, South Buru Regency which aims to form a moral personality for students with Islamic character and personality values. However, the personality of the students has not been formed optimally so that delinquency often occurs, even though it is still included in the mild crime category, PAI teachers have the responsibility for how to fix problems that occur in students, for example: coming late to school, skipping school, brawls between students students, brawls between classmates and violation of school rules. The research method applied in this study is the "descriptive-qualitative" research method. This research was conducted at Alhilaal Siwar Elementary School, Ambalau District, South Buru Regency. The findings show that Islamic Religious Education (PAI) teachers have fulfilled their role as educators in shaping the personality of students at Alhilaal Siwar Elementary School (SD) Alhilaal Siwar District, Ambalau District, South Buru Regency. In shaping the personality of fourth grade students at Alhilaal Siwar Elementary School, Islamic Religious Education (PAI) teachers took the initiative to improve the personalities of their students such as correcting students' actions and correcting all their shortcomings to provide good inspiration and motivation for the progress of their students.